2001
DOI: 10.1111/1467-8586.00131
|View full text |Cite
|
Sign up to set email alerts
|

The CES‐‐Translog Production Function, Returns to Scale and AES

Abstract: The translog functional form imposes no a priori restrictions on the substitution possibilities between the factor inputs, by relaxing the assumption of strong separability, and the CES± translog cost function specification allows for testing homothetic technology with Hicks-neutral technical change. In this paper an n-factor CES ± translog production function is presented which develops the parameters to directly assess scale effects from those due to technology in the production structure. In addition, by ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The production function can follow either the Cobb-Douglas functional form or the translog functional form. The translog functional form is generally specified as (Kymn and Hisnanick 2001):…”
Section: The Stochastic Frontier Modelmentioning
confidence: 99%
“…The production function can follow either the Cobb-Douglas functional form or the translog functional form. The translog functional form is generally specified as (Kymn and Hisnanick 2001):…”
Section: The Stochastic Frontier Modelmentioning
confidence: 99%
“…Several studies found the translog specification preferable to the Cobb-Douglas. Tzouvelekas (2000) and Kymn and Hisnanick (2001) could not reject the translog in favor of the Cobb-Douglas. Heyer et al (2004) also found the translog superior when accounting for factor utilization.…”
Section: Modeling Of Efficiencymentioning
confidence: 98%
“…3 only contains the linear coefficient input variables without including derivative variables such as interactions and quadratic forms of production input variables. However, the translog production function is superior to the Cobb-Douglas function in approximating unknown production functions (Kymn & Hisnanick, 2001;Shih et al, 1977). The translog relaxes strong assumptions of the Cobb-Douglas like homotheticity, homogeneity and separability (Kymn & Hisnanick, 2001;Tzouvelekas, 2000).…”
Section: Modeling Of Efficiencymentioning
confidence: 99%
See 2 more Smart Citations